Bridging Engineering and Ethics: A Framework for Responsible AI-Driven Software Development (Al-Farooq Journal of Sciences, 2026)
The integration of Artificial Intelligence (AI) into software systems has witnessed rapid evolution, yielding substantial benefits for society; however, it has concurrently given rise to serious ethical challenges. This paper explores the necessity of adopting the concepts of "Ethical AI" and "Responsible Software Development" to ensure the alignment of technological innovations with human values and societal well-being. The study examines prominent issues such as lack of transparency, privacy infringement, and environmental impacts, emphasizing the urgent need for frameworks to govern the practices of developing and deploying AI systems. Drawing upon previous studies and industrial policies, the paper proposes a comprehensive model for integrating ethical standards into the phases of the Software Development Life Cycle (SDLC). This model is founded on the pillars of fairness, transparency, accountability, and sustainability, offering practical recommendations aimed at developers, organizations, and policymakers. By presenting this systematic approach, the paper aims to enrich the ongoing discourse on AI ethics, build trust, and promote inclusivity and sustainable societal benefit
Keywords: Artificial Intelligence, Software Development, Software Engineering, Privacy